The impact of physical activity on arterial stiffness and inflammation; results from the "Corinthia" study. (14th October 2021) - Theofilis, P; Oikonomou, E; Vogiatzi, G; Lazaros, G; Mystakidi, V X; Goliopoulou, A; Anastasiou, M; Tsalamandris, S; Chasikidis, C; Papakonstantinou, M; Fountoulakis, P; Christoforatou, E; et al.
Abstract: Background: Diminished physical activity (PA) is associated with cardiovascular morbidity and mortality. Arterial stiffness and inflammation are associated with atherosclerosis and are established risk factors for cardiovascular disease. Purpose: We investigated the association of PA status on arterial stiffness and inflammation. Methods: Classification of PA was performed in 2053 participants of the cross-sectional "Corinthia" study using the International Physical Activity Questionnaire (IPAQ). In accordance with the standard IPAQ scoring procedures, participants were classified into one of the following groups: upper tertile: "vigorous" PA-IPAQ 2, middle tertile: "moderate" PA-IPAQ 1 or lower tertile: "low" PA-IPAQ 0. Arterial stiffness was estimated via carotid-femoral pulse wave velocity (cfPWV) estimation and inflammatory burden was assessed via high sensitivity C reactive protein (hsCRP) measurement. Results: Participants with low PA had impaired cfPWV values (IPAQ 0: 9.5±3.2 m/s vs. IPAQ 1: 8.7±2.4 m/s vs. IPAQ 2: 8.7±2.2 m/s, p<0.001) (Figure 1, Panel A) while abnormal cfPWV –adjusted for age and blood pressure- were more frequently encountered in low PA individuals (IPAQ 0: 14% vs. IPAQ 1: 7.8% vs. IPAQ 2: 7.3%, p=0.001) (Figure 1, Panel B). Participants characterized as having vigorous physical activity had the lowest inflammatory burden, as estimated by hsCRP (IPAQ 0: 4.8±6.4 g/l vs. IPAQ 1: 4.6±5.2 g/l vs. IPAQ 2: 3.6±4.2 g/l, p=0.001) (Figure 1, Panel C). Importantly, results remained unaffected even after adjustment for confounders (Figure 1, Panel D). A correlation analysis between the total weekly physical activity (expressed as MET minutes/week) and arterial stiffness was performed demonstrating a statistically significant negative correlation was noted (r=−0.120, p<0.001) (Figure 1, Panel E). Conclusion: A significant association between physical activity, arterial stiffness and inflammation was observed, even after adjusting for known cardiovascular risk factors. Our findings should raise public awareness about the beneficial effects of exercise on cardiovascular health. FUNDunding Acknowledgement: Type of funding sources: None.